An exploratory study of Slum Development projects in Dhaka city: a case study of UBSDP and WATSAN - Khan, Shakila Parveen (Masters of Development studies, BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master of Development Studies, 2007.